JUDICIAL INTERPRETATION CHALLENGES IN IMPLEMENTING CHILD PROTECTION RIGHTS OUTSIDE OF MARRIAGE: A STUDY OF THE RELIGIOUS COURT OF MALANG REGENCY - Zaman, Jamrud Qomaruz; Rouf, Abd.; Samudin, Siti Aisyah binti; Saifullah, Ainan Husnaa binti Muhammad (istinbath, 2025)
Constitutional Court Decision No. 46/PUU-VIII/2010 is classified as a positive legislator decision and is not followed up by lawmakers, making it difficult to apply, especially the interpretation of the phrases ‘children born outside marriage’ and ‘civil relations’. The purpose of this study is to examine the judges' interpretation model of children outside marriage and their civil rights in Constitutional Court Decision No. 46/PUU-VIII/2010 with the indicators of François Gény’s legal contextualization theory. This research is mixed research with legislative, legal philosophy, and sociology approaches. The data analysis technique used is descriptive-analytical. The result of this research is that the phrase “children born out of wedlock” in Constitutional Court Decision No. 46/PUU-VIII/2010 is often understood differently by the panel of judges, some of whom limit it only to children born out of siri marriage as guided by Islamic law. However, some also extend it to children born of adultery on the grounds of children's human rights. Although ideally, both of the judges' reasoning is by François Gény's theory of legal contextualization, in reality, the narrowing of the meaning to children from siri marriages is closer to the truth due to the context of the applicant's status as a siri marriage and the contextualization of Indonesian society today which is always religious. Therefore, the phrase “children born out of wedlock” in Constitutional Court Decision No. 46/PUU-VIII/2010 must be interpreted narrowly to children from siri marriages.